LIFE TABLE, RATE OF INCREASE AND STABLE-AGE DISTRIBUTION OF PLUTELLA XYLOSTELLA (LINN.) ON KNOL KHOL - HEMCHANDRA, O.; SINGH, T.K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2004)
Studies on life table, rate of increase and stable-age distribution for the Plutella xylostella were carried out in laboratory on knol khol during February and March 2000, At Department of Life Sciences, Manipur University, Canchipur. The numbers that survived from egg to adult emergence was worked out. The net reproductive rate (R) was 19.2303 representing total birth with a mean length of generation (T,) being 32.542. The population increase with intrinsic rate of increase (r) was 0.092.12 and finite rate of increase ().) was 1.09649 females per female per day. On reaching the stable-age distribution the population comprised mainly of immature stages and further life at the time of adult emergence was reduced from 9.51 to 5.27.